Incongruous Entertainment : Camp, Cultural Value, and the MGM Musical - Cohan, Steven, 1948- (Book collections on Project MUSE., 2005)
A look at the camp cult appeal of MGM musicals of the 1940s and 50s to gay men today, along with an historical analysis of the films' production histories.